The great land rush and the making of the modern world, 1650-1900 - Weaver, John C. (McGill-Queen's University Press, 2003)
He also underscores the tragic history of the indigenous peoples of these regions and shoes how they came to lose "possession" of their land to newly formed governments made up of Europeans with European interests at heart. Weaver shows that the enormous efforts involved in defining and registering large numbers of newly carved-out parcels of property for reallocation during the Great Land Rush were instrumental in the emergence of much stronger concepts of property rights and argues that this period was marked by a complete disregard for previous notions of restraint on dreams of unlimited material possibility. Today, while the traditional forms of colonization that marked the Great Land Rush are no longer practiced by the European powers and their progeny in the new world, the legacy of this period can be seen in the western powers' insatiable thirst for economic growth, including newer forms of economic colonization of underdeveloped countries, and a continuing evolution of the concepts of property rights, including the development and increasing growth in importance of intellectual property rights.